Eksploitasi Lingkungan dalam Novel Misteri Hilangnya Penyu di Pulau Venu Karya Wini Afiati : (Perspektif Ekokritik Greg Garrard) - Cahyo, Anggoro Abiyyu Ristio; Rengganis, Ririe; Sudikan, Setya Yuwana (Edukasi Lingua Sastra, 2024)
Wini Afiati's children's novel The Mystery of the Disappearance of the Turtle on Venu Island tells the story of a family who has just moved to the town of Kaiman, West Papua. The area is close to Venu Island. Venu Island is where the father character works as a marine conservation supervisor. However, there is an unexpected phenomenon, turtles that should be protected are stolen by a group of people. This study aims to describe (1) the causes of damage to the physical environment, (2) the human bond with the physical environment, and (3) the values of ecological wisdom in the children's novel Misteri Hilangnya Penyu di Pulai Venu by Wini Afiati. These objectives are closely related to Greg Garrard's concept of ecocriticism. The type of research used in this study is qualitative research with descriptive method. The data collection technique used in this research is reading and note-taking technique. The data analysis technique used is hermeutics. The hermeutic technique focuses on the text objectively. The results of this study are the causes of damage to the physical setting of the environment caused by irresponsible humans, human bonds that care about the surrounding environment, and ecological wisdom created in society.Keywords: ecocriticism, damage, bonding, wisdom, ecological.